Bulletin / International Socialist Committee for the Organized Jewish Workers in Palestine
French ed.: Bulletin. Comité socialiste pour la Palestine ouvrière. (ZK 16234). - German ed.: Bulletin. Socialistisches Komitee fuer das arbeitende Palastina. (ZK 16235).